1985
DOI: 10.1093/infdis/152.4.727
|View full text |Cite
|
Sign up to set email alerts
|

Selective Defects in Cytomegalovirus- and Mitogen-Induced Lymphocyte Proliferation and Interferon Release in Patients with Acquired Immunodeficiency Syndrome

Abstract: To examine the defect in cellular immunity in patients with acquired immunodeficiency syndrome (AIDS), we studied in vitro lymphocyte proliferation and interferon (IFN) release in response to cytomegalovirus (CMV) antigen and Concanavalin A mitogen in 40 homosexual men with AIDS, 10 homosexual men with chronic lymphadenopathy syndrome, 7 healthy homosexual men, and 18 healthy heterosexual subjects of either sex. CMV serology by an enzyme-linked immunosorbent assay and viral cultures for CMV were performed. Lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…A reduction in the proliferative capacity of CD4 ϩ T lymphocytes in response to HIV antigens has been demonstrated (9,15,18,19,23,24). HIV type 1 (HIV-1) replication also inhibits antigen-specific CD4 ϩ T-lymphocyte progression through the cell division cycle (26).…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in the proliferative capacity of CD4 ϩ T lymphocytes in response to HIV antigens has been demonstrated (9,15,18,19,23,24). HIV type 1 (HIV-1) replication also inhibits antigen-specific CD4 ϩ T-lymphocyte progression through the cell division cycle (26).…”
Section: Cd4mentioning
confidence: 99%
“…HIV type 1 (HIV-1) replication also inhibits antigen-specific CD4 ϩ T-lymphocyte progression through the cell division cycle (26). Finally, a loss of the CD4 ϩ T lymphocytes' ability to secrete cytokines in response to viral antigen stimulation has been described in infected individuals (9,17). Since activated CD4 ϩ T cells are infected and destroyed by HIV-1, these sequelae of infection are not surprising (8,27).…”
Section: Cd4mentioning
confidence: 99%
“…It has long been appreciated that HIV-1 infection is associated clinically with a gradual decline in CD4 ϩ T-lymphocyte numbers and an impairment of CD4 ϩ T-lymphocyte function (3,12,20). Recent studies have shown that control of viral replication in vivo is associated with vigorous HIV-1-specific CD4 ϩ T-lymphocyte proliferative responses (28).…”
Section: Cd4mentioning
confidence: 99%
“…Interpreting studies of CD4 ϩ T-lymphocyte responses elicited by an AIDS virus infection can, however, prove problematic. An AIDS virus infection, by virtue of the capacity of the virus to lyse and cause functional abnormalities of CD4 ϩ T cells, is associated with a very-low-frequency, dysfunctional CD4 ϩ T-lymphocyte response (3,12,20). We therefore chose to study the responses of CD4 ϩ T lymphocytes to AIDS viruses that are nonpathogenic and other AIDS viruses that are pathogenic but do not cause profound CD4-cell depletion (5,6,25,26).…”
Section: Fig 2 Tetramericmentioning
confidence: 99%
“…In addition, it is known that for CMV, CD8 as well as CD4 T cells proliferate when cultured with CMV infected cells (as antigen) (9, 10). In those immunosuppressed by HIV, Wahren et al (1987) and others (I1, 12,13) found that, on average, T cells from HIV (and CMV) infected donors had lower levels of T cell proliferation to CMV antigen in vitro than did cells from CMV-infected, HIV seronegative controls. However, within these average lower responses, there is considerable individual variation.…”
mentioning
confidence: 98%